Wire brushing wood furniture, granulomatosis and microscopic mineralogical analysis - Catinon, Mickaël; Chemarin, Cécile; Assaad, Souad; Vuillermoz-Blas, Sylvie; Roux, Elisabeth; Traverse-Glehen, Alexandra; Cavalin, Catherine; Rosental, Paul-André; Vincent, Michel (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2014)
IntroductionThere is increasing evidence that sarcoidosis can occur in workplaces in which there is exposure to inorganic triggers (1-3). Moreover, transmission electron microscopy (TEM) and energy dispersive X-ray (EDX) analysis may contribute to identifying micro and/or nanoparticles in granulomatous tissues  (4-6) and, out of the workplace, hobby activities may also involve dangerous exposure...